EVALUATION OF COMMUNITY PHARMACIST INTERVENTIONS IN DIABETES AND BLOOD PRESSURE MANAGEMENT - Asiya Saif Asiya; Maria Gul; Tangina Malik Tangina; Mubashra Gul (International Journal of Pharmacy & Integrated Health Sciences)
Background: The pharmacist community played a significant role in serving the nation for many years. The total number of registered pharmacists by the provincial pharmacy council is 23029. The role of pharmacists and their services is unrecognized by society. Aims:  The intention of this clinical project is to create awareness among the population regarding the pharmacist's role in improving the health of the patients and disease management. The aim is to highlight the importance of pharmacists among patients regarding their medication therapy and lifestyle modification to provide clear evidence of health gain. Methodology: It is a non-experimental based questionnaire study which is performed in community pharmacy and medical stores of Lahore, Islamabad, Gujranwala and Sargodha. Most of the people in Pakistan visit medical stores for the grant of medication without pharmacist advice in rural areas of Punjab Pakistan. But in big cities such as Lahore, Islamabad people visit pharmacies for grant of their medication and in some pharmacies pharmacist counsel the patient regarding their medication and visit a pharmacist are more satisfied and feel improvement in their condition. Results: Patients were divided in two group, one who visited medical store and other who went to pharmacy. We are interested in patients who are visiting the pharmacy and getting the various type of benefits from the presence of pharmacist. Conclusion Diabetes and hypertension are two major chronic diseases and spread widely across the world including Pakistan. In the management of diabetes and hypertension pharmacist interventions are beneficial and literature study provide evidence of it. People who visit a pharmacy also get economic benefit as pharmacist also offer alternatives which costs lesser.